The Maximization of State Non-Tax Receivables Management at The Directorate General of Law Enforcement on Environment and Forestry - Perangin-angin, Anastasia; Silitonga, Mala Sondang (Jurnal Borneo Administrator, 2024)
This research investigates the problems encountered in the receivables management process by outlining the main strategies at the Directorate General of Environmental and Forestry Law Enforcement (Dirjen PHLHK). This research uses a qualitative approach and case study method. The results of this study indicate that the process of managing receivables at Dirjen PHLHK has not been optimal due to the absence of a formal SOP for receivables management, limited human resources, inefficient coordination and cooperation between internal divisions and external institutions, ineffective internal control, and inadequate facilities. Therefore, the efforts to optimize accounts receivable management at Dirjen PHLHK include making formal SOPs, making operational guidelines and technical guidelines for the implementation of receivables management, compiling a more comprehensive workload according to position class, recruiting officers who meet the qualifications of tasks and functions related to accounts receivable management, increasing awareness among related parties, implementing a more active internal control system and developing facilities and infrastructure in the implementation of receivables management by implementing a more sophisticated and sustainable technology system. The implications of the study are thoroughly discussed.